Effects of respiratory therapeutics and physical activity in maximal respiratory pressures of obese women - M.S.L. Cruz; P. Roquetti Fernandes; E. Sonehara; V.M. Reis; F.B. Policarpo; J. Fernandes Filho (Desafio Singular, 2010)
The aim of this study was to evaluate the effects of differing therapies on maximal static respiratory pressure in 51 obese women divided into three groups: i) sedentary women (n = 19, aged 57.37 ± 8.10 years, BMI = 38.3± 5.9); ii) physically active women (n = 13, aged 60.31 ± 8.94 years, BMI = 38.0 ± 7.7) submitted to seven days of therapy through incentive spirometry, and iii) women in pulmonary rehabilitation (n = 20, aged 48.75 ± 13.71 years, BMI = 34.7±3.8) submitted to a 12-week program of aerobic physical activity at 70% heart rate reserve, and breathing and stretching exercises. Data were treated using a one way ANOVA with post-hoc Turkey, within groups with paired t test and Pearson's correlation coefficient. Results showed a significant post-therapy (p < .05) for the maximal static respiratory pressure between and within group with significant changes on obese women's maximal static respiratory pressure.